Marketing Communication Channels and Consumer Purchase Intention: The Role of Brand Trust in Air Tanzania - Peace Faustine Tibanyendera (Program Studi Pendidikan Ekonomi FKIP Universitas Lambung Mangkurat, 2026)
The growing fragmentation of marketing communication channels has compelled firms in the airline industry to reassess how social and traditional media affect customer behavior. This study observes which role do marketing communication media play in influencing consumer purchase intentions, with brand trust serving as a key explanatory mechanism. Data were acquired using quantitative approaches, using a structured questionnaire distributed to Tanzanian airline customers. The suggested research model was validated with partial least squares structural equation modeling (PLS-SEM). The data indicate that both media marketing channels have a significant impact on brand trust and customer purchase intentions. Also, brand trust was found to play a critical role in strengthening the relationship between marketing communication media and purchase intentions. These results suggest that coordinated use of traditional and digital marketing channels can enhance consumer confidence and purchasing decisions in the airline industry. The study contributes to the marketing and entrepreneurship literature by offering concrete proof from a developing market environment, as well as practical recommendations for airline executives looking to increase advertising efficiency and customer trust.